Chapitre 2. Le mouvement anti-esclavagiste et la naissance des droits des femmes. - Davis, Angela Yvonne (Femmes, race et classe, 1983)
Etude socio-historique de la condition des femmes noires aux Etats-Unis; aspect particulier de l'esclavage des femmes noires; persistance des problèmes après l'abolition de l'esclavage.
Section: 341 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; corps; cours; discipline; droits des femmes*; esclavagisme; féminisme afroaméricain; féminismes noirs; histoire et politique; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; états-unis

L'héritage de l'esclavage : éléments pour une autre approche de la condition de femme - Davis, Angela Yvonne (Femmes, race et classe, 1983)
Etude socio-historique de la condition des femmes noires aux Etats-Unis; aspect particulier de l'esclavage des femmes noires; persistance des problèmes après l'abolition de l'esclavage.
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; cours; esclavagisme; fem1000; femmes* afro-américaines; féminismes noirs; inégalités; justice sociale; premier cycle; racisme; régions géographiques; systèmes d'oppressions; états-unis

Resistance to oppression: Black women's response to slavery in the united states - Ellison, Mary (Slavery & Abolition, 1983)
Keywords: afro-féminisme; amériques; approches et analyses; cours; esclavagisme; fem3100; femmes* afro-américaines; féminisme afroaméricain; histoire et politique; militance; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

La place - Ernaux, Annie (Gallimard, 1983)
«Récit remarqué par la critique. L'ombre du père et la genèse d'un remord, celui d'une intellectuelle d'origine modeste devenue "bourgeoise". Prix Renaudot 1984.»– [SDM].
Section: 113 pages
Keywords: 1900-1999; arts; cours; discipline; disicpline; europe; filiation; france; lit2815; premier cycle; périodes historiques; roman; régions géographiques; thématiques; transfuge de classe; écriture des femmes*; études littéraires

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Boréal Express, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Le texte suivant : Owens, Craig. (1983). The Discourse of Others: Feminists and Postmodernism, 57-82 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Section: xvi, 175 pages ; 22 cm
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Discovering reality : feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science - Harding, Sandra G.; Hintikka, Merril B. (D. Reidel, 1983)
This collection of essays, first published two decades ago, presents central feminist critiques and analyses of natural and social sciences and their philosophies. This work provides a splendid opportunity for upper-level undergraduate and graduate students in philosophy and the social sciences to explore some of the most intriguing and controversial challenges to disciplinary projects and to public policy today.
Keywords: approches et analyses; cours; discipline; discours dominant; fem1000; philosophie; point de vue situé; premier cycle; sciences humaines; systèmes d'oppressions; épistémologie

The feminist standpoint: Developing the ground for a specifically feminist historical materialism - Hartstock, Nancy (Discovering reality: Feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science, 1983)
Keywords: approches et analyses; cours; discipline; fem1000; féminisme matérialiste; philosophie; point de vue situé; premier cycle; sciences humaines; épistémologie

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Section: 64 p. : ill. (certaines en coul.)
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques

Nous sommes le produit d’un contexte - O'Leary, Véronique; St-Pierre, Josée.; Toupin, Louise (Québécoises deboutte! Tome 1. Une Anthologie de textes du Front de libération des femmes (1969-1971) et du Centre des femmes (1972-1975)., 1983)
Le volume 1 (212 p.) comprend des tracts, documents internes, manifestes et lettres diffusées par les deux groupes entre 1969 et 1975, de même qu'un aperçu de la couverture de presse dont ils bénéficièrent à l'époque. Le volume 2 (377 p.) reprend la collection complète du journal ##Québécoises deboutte## publié entre 1972 et 1975, par le Centre des femmes; on y a ajouté des tables rondes.
Section: 2 volumes : illustrations ; 28 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; histoire et politique; inégalités; militance; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques

La Québécoite: roman - Robin, Régine (Québec-Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Section: 200 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"–
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Le système - Saint-Jean, Armande (Pour en finir avec le patriarcat, 1983)
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Pour en finir avec le patriarcat - Saint-Jean, Armande (Primeur, 1983)
Essai théorique et document journalistique à la fois, Pour en finir avec le patriarcat apporte une réponse sereine et engagée à vos questions de tous les jours
Keywords: 1900-1999; amériques; approches et analyses; classe sociale; cours; discipline; fem1000; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions

Powers of desire the politics of sexuality - Snitow, Ann Barr; Stansell, Christine; Thompson, Sharon (Monthly Review Press, 1983)
This provocative anthology brings together a diverse group of well-known feminist and gay writers, historians, and activists. They are concerned not only with current sexual issues-abortion, pornography, reproductive and gay rights-but they also raise a host of new issues and questions: How, and in what ways, is sexuality political? Is the struggle for sexual freedom a complement to other struggles for liberation, or will it detract from them? Has the sexual revolution diminished or enriched the lives of women?
Section: 489 p.
Keywords: approches et analyses; cours; discipline; histoire; intersectionnalité; justice sociale; lesbianisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; thématiques; études féministes

In search of our mothers' gardens womanist prose - Walker, Alice (Harcourt Brace, 1983)
In this, her first collection of nonfiction, Alice Walker speaks out as a black woman, writer, mother, and feminist. Among the thirty-six pieces are essays about other writers, accounts of the civil rights movement of the 1960s and the anti-nuclear movement of the 1980s, and a vivid memoir of a scarring childhood injury and her daughter’s healing words.
Keywords: 1900-1999; amériques; approches et analyses; arts; cours; cycles supérieurs; discipline; droits civiques; fem1000; fem3300; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; womanist; états-unis; études littéraires